2020
DOI: 10.3389/fonc.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for Metastasis in Prostate Cancer: A Review of the Literature

Abstract: Background: Initial staging and assessment of treatment activity in metastatic prostate cancer (PCa) patients is controversial. Indications for the various available imaging modalities are not well-established due to rapid advancements in imaging and treatment. Methods:We conducted a critical literature review of the main imaging abnormalities that suggest a diagnosis of metastasis in localized and locally advanced PCa or in cases of biological relapse. We also assessed the role of the various imaging modaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 105 publications
(114 reference statements)
0
43
0
3
Order By: Relevance
“…Importantly, that review suggested that WMBRI could be more sensitive than PET/CT for visceral metastases (28)(29)(30) and small hepatic and brain metastases (28,31,32), but WBMRI could be associated with more false-positives that PET/CT for bone metastases because bone marrow edema caused by benign lesions can appear as metastases on the apparent diffusion coefficient (ADC) map (28). A review highlighted that modern PET/CT protocols have a better diagnostic value than MRI for the detection of PCa metastases but that MRI still has a role to play (33). Since the present meta-analyses only examined bone metastases, this edema from benign lesions might explain, at least in part, why WBMRI fared less well than PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, that review suggested that WMBRI could be more sensitive than PET/CT for visceral metastases (28)(29)(30) and small hepatic and brain metastases (28,31,32), but WBMRI could be associated with more false-positives that PET/CT for bone metastases because bone marrow edema caused by benign lesions can appear as metastases on the apparent diffusion coefficient (ADC) map (28). A review highlighted that modern PET/CT protocols have a better diagnostic value than MRI for the detection of PCa metastases but that MRI still has a role to play (33). Since the present meta-analyses only examined bone metastases, this edema from benign lesions might explain, at least in part, why WBMRI fared less well than PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Significant advances have been made in imaging for metastatic prostate cancer, with increasing use of PSMA-PET and WBMRI adding increased sensitivity and anatomical delineation of metastases. 4 Despite this, bone scans will remain an affordable method that allows treatment decisions to be made based on the volume of disease present. Novel imaging tools may not be affordable to or available in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although IBS has limited sensitivity (79%) and specificity (82%) for detection of bone metastases, 3,4 it is still the most frequently used method for diagnosis to assess skeletal involvement in prostate cancer. A validated endpoint in mCRPC trials is bone scan progression, which relies on the appearance of new lesions, as proposed by the prostate cancer working group 3 (PCWG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer (PC) is the most frequently diagnosed cancer in 105 countries in men and is the most common cause of death from malignant tumours [ 56 ]. Most PCs are curable, but metastatic forms are associated with lower survival rate; therefore, imaging is needed to detect and track metastases evolution during treatment [ 57 ].…”
Section: Different Cancersmentioning
confidence: 99%